Tumor necrosis factor receptor regulation of peripheral node addressin biosynthetic components in tumor endothelial cells - Rodriguez, Anthony B.; Parriott, Geoffrey; Engelhard, Victor H. (Frontiers in Immunology, 2022)
Tumor-associated tertiary lymphoid structures are ectopic lymphoid aggregates that have considerable morphological, cellular, and molecular similarity to secondary lymphoid organs, particularly lymph nodes. Tumor vessels expressing peripheral node addressin (PNAd) are hallmark features of these structures. Previous work from our laboratory demonstrated that PNAd is displayed on intratumoral vasculature of murine tumors, and its expression is controlled by the engagement of lymphotoxin-α3, secreted by effector CD8 T cells, with tumor necrosis factor receptors (TNFR) on tumor endothelial cells (TEC). The goals of the present work were: 1) to identify differences in expression of genes encoding the scaffolding proteins and glycosyl transferases associated with PNAd biosynthesis in TEC and lymph node blood endothelial cells (LN BEC); and 2) to determine which of these PNAd associated components are regulated by TNFR signaling. We found that the same genes encoding scaffolding proteins and glycosyl transferases were upregulated in PNAd+ LN BEC and PNAd+ TEC relative to their PNAdneg counterparts. The lower level of PNAd expression on TEC vs LN BEC was associated with relatively lower expression of these genes, particularly the carbohydrate sulfotransferase Chst4. Loss of PNAd on TEC in the absence of TNFR signaling was associated with lack of upregulation of these same genes. A small subset of PNAd+ TEC remaining in the absence of TNFR signaling showed normal upregulation of a subset of these genes, but reduced upregulation of genes encoding the scaffolding proteins podocalyxin and nepmucin, and carbohydrate sulfotransferase Chst2. Lastly, we found that checkpoint immunotherapy augmented both the fraction of TEC expressing PNAd and their surface level of this ligand. This work points to strong similarities in the regulation of PNAd expression on TEC by TNFR signaling and on LN BEC by lymphotoxin-β receptor signaling, and provides a platform for the development of novel strategies that manipulate PNAd expression on tumor vasculature as an element of cancer immunotherapy.